Competing for Tomorrow’s Customers: A View from the Future - Church, Nancy J. (Mercados y Negocios, 2019)
This paper includes a compilation of the most important activities that marketers will need to perform in order to be competitive in the coming years. As changes occur and new competitive processes or practices are developed, practitioners often create acronyms that come into general use as a type of shorthand. This paper will discuss several acronyms that have become central to competing for tomorrow’s customers. The purpose of this investigation is to provide marketing professionals with important information about where they will need to focus their efforts, update their knowledge, and continue to build their marketing skill sets if they are to succeed in the future and to provide business professors with leading edge information so that they can best prepare their marketing students to be highly competitive when they graduate and enter the business world.